Physical and mechanical performance of PU and PRF adhesive in cross laminating of Dark Red Meranti - Muhammad, Nur Nabilah (2019)
Cross Laminated Timber (CLT) are widely used in European countries in the construction of conventional buildings. However, solid wood has different durability, strength and characteristics. Therefore, choosing the right wood species should be especially important in making a study. Among the selected species of wood in this study are wood species from specific gravity 5 (SG) groups. In this test, there are two tests involved, namely the Flexural Strength Test where this test uses four bending static bending and where delamination tests is to determine the measure the level of failure of adhesion when the samples immersed in water. The data is analyzed using "Statistical Package for the Social Sciences" (SPSS). PRF is the adhesive that provides the highest strength and the most elastic compared to PU type adhesive.